(untitled) (Health Renaissance, 2013)
Background: Tobacco use as a habit by females and during pregnancy not only affects the maternal health but has negative impact on fetal health as well, but so far there has been few studies related to this issue in Nepal. No study of such type has been done in the Eastern Development region of Nepal. Objectives: This study was designed with the objectives to measure the proportion of women using tobacco during pregnancy among the patients enrolled and to compare the pregnancy course and socio-demographic variables between tobacco users and non users. Methods: Appropriate sample of 234 women selected from postnatal wards of Dhankuta and Sunsari district hospitals and Teaching Hospital of B P Koirala Institute of Health Sciences (BPKIHS) in the eastern Nepal from July 2009 to June 2010. They were interviewed and the data analyzed on SPSS 17 version. Results: The study revealed that the prevalence of tobacco use during pregnancy was 19.2 percent. Maximum number of the tobacco users was found in the age group of 20-29 years during their pregnancy. More than 73% of tobacco users were below the poverty line. Conclusion: No significant association was seen between the use of tobacco during pregnancy and events during pregnancy like abortion, pre term delivery, peri-natal mortality, low birth weight etc. And also, no significant difference was observed in health problem among the participants in between the groups. Health Renaissance, January-April 2013; Vol. 11 No.1; 157-161 DOI: http://dx.doi.org/10.3126/hren.v11i2.8225